Pemberdayaan Masyarakat Padukuhan Malangrejo dalam Pemanfaatan Pewarna Alami Makanan - Paramita Sari, Indah; Hidayat, Rheina Faticha Asyamsa; Afifah, Fitri Nur; Lanjar; Sarbini; Hartati, Yuni; Pratiwi, Rarastoeti (Warta LPM, 2024)
The Community Service Activities for the Independent Campus Learning Program (PkM MBKM), which involves lecturers and students has been done. The program aims to empower the people of Padukuhan Malangrejo, Wedomartani, Ngemplak Sleman, regarding the use of natural dyes for healthy food products. The targets during this program were 14 Women Farmers Group (KWT) participants, 10 elementary school students and 10 teenagers. In this course, we did the socialization of the activities, increasing the community literacy about natural food coloring and its benefits for health, by using the learning modules for children, adolescents and members of Women Farmer Groups (KWT). The training was carried out on the production of natural dyes that can be stored, as well as the creation of colorful food and drink recipes. Evaluation of literacy activities is assessed from understanding the material at the beginning (pre-test) and end (post-test) of the activity. Food products with natural dyes were organoleptically tested in communities outside Malangrejo. Other activities include assistance in the production of BiTel pudding (beetroot and butterfly pea coloring) with limited marketing, obtaining a Hygiene and Sanitation Certificate (SLHS) from the Health Service, Sleman. Activities to plant natural food dyes are carried out in yards and less productive land. Planting methods were adjusted to the type of plant, both horizontally and vertically. The results of the activity showed an increase in community participation and understanding of the benefits of natural food coloring (16.4%), increased literacy in the youth group (4%), KWT participants (2.9%), while for elementary school students there were 40% of participants who got a score of 100 %. This activity also gave rise to Micro, Small and Medium Enterprises (MSMEs or UMKM) which produce food with natural dyes, as well as the enthusiasm of KWT Malangrejo members in using their home gardens to produce natural food dyes. The MBKM PkM program for village development, which was implemented in Padukuhan Malangrejo, was well appreciated by the community and the Wedomartani Village leader, and hopefully the programs will continue in the following year.